Trimethylamine modulates dauer formation, neurodegeneration, and lifespan through tyra‐3/daf‐11 signaling in Caenorhabditis elegans. Issue 5 (5th April 2021) - Khanna, Amit; Sellegounder, Durai; Kumar, Jitendra; Chamoli, Manish; Vargas, Miguel; Chinta, Shankar J.; Rane, Anand; Nelson, Christopher; Peiris, T. Harshani; Brem, Rachel; Andersen, Julie; Lithgow, Gordon; et al.
Abstract: In the nematode Caenorhabditis elegans, signals derived from bacteria in the diet, the animal's major nutrient source, can modulate both behavior and healthspan. Here we describe a dual role for trimethylamine (TMA), a human gut flora metabolite, which acts as a nutrient signal and a neurotoxin. TMA and its associated metabolites are produced by the human gut microbiome and have been suggested to serve as risk biomarkers for diabetes and cardiovascular diseases. We demonstrate that the tyramine receptor TYRA‐3, a conserved G protein‐coupled receptor (GPCR), is required to sense TMA and mediate its responses. TMA activates guanylyl cyclase DAF‐11 signaling through TYRA‐3 in amphid neurons (ASK) and ciliated neurons (BAG) to mediate food‐sensing behavior. Bacterial mutants deficient in TMA production enhance dauer formation, extend lifespan, and are less preferred as a food source. Increased levels of TMA lead to neural damage in models of Parkinson's disease and shorten lifespan. Our results reveal conserved signaling pathways modulated by TMA in C. elegans that are likely to be relevant for its effects in mammalian systems. Abstract : TMA alters development, aging and neurodegeneration in C. elegans . Observed results suggests that the bacterial metabolite TMA alters development, aging and neurodegeneration in C. elegans through DAF‐11 and DAF‐16 pathways.